2021
DOI: 10.1007/s40120-021-00245-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment Profiles, Clinical Outcomes, and Healthcare Resource Utilization of Patients with Migraine Prescribed Erenumab: A Multicenter Chart-Review Study of US Headache Centers

Abstract: Introduction Erenumab, a first-in-class monoclonal antibody targeting the calcitonin gene-related peptide pathway, was approved by the US Food and Drug Administration in 2018 for the prevention of migraine in adults. There is limited data available on its impact in real-world settings. The study aim was to characterize the real-world treatment profiles, clinical outcomes, and healthcare resource utilization of patients prescribed erenumab from select major US headache centers. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…A number of "real-world" studies and registries of migraine treatment with erenumab in North American (18)(19)(20)(21)(22)(23)(24)(25), European (26)(27)(28)(29)(30)(31)(32)(33), or Australian patients (34) have been published recently and included mainly patients with CM (Supplementary Table 1). With one exception (21), all the studies from North America were retrospective (18-20, 22, 23, 26), while all studies but two (26,30) studies from other geographic areas had a prospective design.…”
Section: Discussionmentioning
confidence: 99%
“…A number of "real-world" studies and registries of migraine treatment with erenumab in North American (18)(19)(20)(21)(22)(23)(24)(25), European (26)(27)(28)(29)(30)(31)(32)(33), or Australian patients (34) have been published recently and included mainly patients with CM (Supplementary Table 1). With one exception (21), all the studies from North America were retrospective (18-20, 22, 23, 26), while all studies but two (26,30) studies from other geographic areas had a prospective design.…”
Section: Discussionmentioning
confidence: 99%
“…Previous real-world studies have demonstrated that CGRP pathway–targeted therapies are effective as preventive treatments for migraine in adults [ 19 22 ]. In a Spanish prospective observational study of 155 migraine patients with ≥ 8 headache days per month and ≥ 3 prior preventive medication failures, treatment with erenumab ( n = 109) or galcanezumab ( n = 46) for 3 months resulted in a ≥ 50% reduction in migraine days per month in 51.6% of patients (mean [SD] reduction in migraine days per month compared with baseline was −8.5 [7.7]) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of 81 Italian patients with high-frequency EM and CM, treatment with galcanezumab for 3 months resulted in a significant decrease in monthly migraine days compared with baseline (EM, −8.5; CM, −11.5; both P < 0.0001) [ 21 ]. A multicenter retrospective chart review of US headache centers evaluated data from 1034 patients with CM [ 19 ]. Results showed that treatment with erenumab for ≥ 3 months resulted in a ≥ 50% reduction in mean headache/migraine days per month among 35% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, in many studies the concomitant use of one or more preventive headache medications was permitted. If the migraine patients continue treatment by a polypharmacy approach including, for instance, opioid receptor agonists, the rate of constipation may be equally high before and after erenumab therapy ( Faust et al, 2021 ).…”
Section: Constipation As An Adverse Effect Of Calcitonin Gene-related Peptide and Calcitonin Gene-related Peptide Receptor Antibodies In mentioning
confidence: 99%
“…A straightforward explanation for the significantly higher constipation rates in migraine patients on a CGRP-targeting therapy under real world conditions as compared to RCT conditions is not yet available. Differences in the patient populations in terms of medical history and comorbidities as well as a more detailed assessment of adverse events and disturbances of life quality are likely to be contributory factors ( Lambru et al, 2020 ; Faust et al, 2021 ). Important information may also be deduced from a future comparison of the real world constipation rates associated with the long-term use of gepants, on the one hand, and antibodies targeting the CGRP system, on the other hand.…”
Section: Mechanistic Basis Of Constipation Caused By Anti-calcitonin Gene-related Peptide Migraine Therapeuticsmentioning
confidence: 99%